Political campaigns in South Africa: Does celebrity endorsement influence the intention to vote?. Issue 2 (29th July 2020) - Madinga, Nkosivile Welcome; Maziriri, Eugine Tafadzwa; Mototo, Lebogang Thato; Chuchu, Tinashe
Abstract : From presidential campaigns to social awareness campaigns, celebrities have gradually become central fixtures in modern politics. They tend to be information platforms for candidates and parties they either clearly support or officially endorse. South African political parties raised eyebrows when they rallied the country's popular celebrities to publicly endorse them. Political parties spend a significant amount of money on celebrity endorsements as it is believed that celebrities can leverage "secondary brand associations". This leads to the question: does the increased use of celebrity endorsements in political campaigns influence the intention to vote? The aim of this study is to investigate the influence of celebrity political endorsement on intentions to vote. Employing a quantitative research design, 227 respondents were surveyed using a structured questionnaire. The findings show that endorser credibility has a positive significant relationship with political party credibility and voters' intentions. The relationship between political party credibility and voters' intentions is also positive and significant. This study provides managerial implications, limitations and future research.